ARCHAEOLOGICAL INVESTIGATIONS AT THE MUGINSKY SITE IN 2021 - Sajpudinov, Murad Sahbanovic; Rabogina, Natal'a Evgen'evna; Borisov, Aleksandr Vladimirovic; Idrisov, Idris Abdulbutaevic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper provides the results of the archaeological exploration of the Muginsky site (Akushinsky district of the Republic of Dagestan) and paleobotanical analysis of the obtained material. As a result of the investigations carried out, various archeological materials, mainly ceramic ware, have been uncovered. The finds of a fragment of a stone mace head and a flint knife-shaped blade are of particular interest. In addition, a large number of animal bones, mainly of small cattle, were found. Exploration of the Muginsky site have provided new and important material for the cultural and historical characteristics of the culture of the central part of Mountainous Dagestan and the chronology of the site, allowed us to determine the two-layered nature of the site and date it to the final phase of the Eneolithic (Layer 4) and the Middle Bronze Age (Layer 3). The radiocarbon dating for Layer 3, with calibration (1770 ± 50 BC), attributes it between the 19th–18th centuries BC. Paleobotanical examination of finds from the cultural layer of the Muginsky site has revealed an atypical combination of barley and rye grains. The rye grains found are the earliest evidence of the presence of this cereal in the Eastern Caucasus, which raises the question of the time and ways of dissemination of this cultivated crop from the primary area. This subject requires further research and obtaining more extensive paleobotanical collections from cultural layers and the resource zone around sites. This will expand our understanding of the economic activities of the local population, such as the development of agriculture and the emergence of terraced agriculture.
Keywords: Eastern Caucasus; Mountainous Dagestan; Mughi settlement; Chalcolite; Middle Bronze age; paleobotanical studies.